The Significance of Screening for Microvascular Diseases in Chinese Community-Based Subjects with Various Metabolic Abnormalities - Pang, Can (Public Library of Science, 2014)
BACKGROUND: To assess the association of albuminuria and retinopathy with metabolic syndrome (MetS) and the related metabolic components defined by various criteria in Chinese community-based subjects. METHODS: A total of 3240 Chinese subjects were recruited from urban communities and classified into subgroups with isolated or concomitant state of the two microvascular diseases. MetS was defined according to the standard of International Diabetes Federation, the National Cholesterol Education Program's Adult Treatment Panel III and Chinese Diabetes Society (CDS), separately. Albuminuria was defined as an elevated morning urine albumin-to-creatinine ratio. Retinopathy were identified with nonmydriatic retinal photographs according to the Diabetic Retinopathy Disease Severity Scale. Logistic regression was performed to analyze the contributive risk factors. RESULTS: The subgroup of isolated retinopathy was the oldest (P<0.05), with higher blood pressure (P<0.001) and larger waist circumference (P<0.05). After adjusting for age, sex and other metabolic components, individuals with blood pressure over 130/85 mmHg were prone to have isolated albuminuria (OR: 1.51, P = 0.0001); while individuals with fasting plasma glucose over 5.6 mmol/L were in high risk of retinopathy concomitant with albuminria (OR: 3.04, P = 0.006). Larger waist circumference was a potential risk factors for isolated albuminuria and isolated retinopathy, though not significant after further adjustment of other metabolic components. The risk for albuminuria and retinopathy increased with the aggregation of three or more metabolic components. However, the MetS per se did not have synergic effect and only the MetS defined by CDS remained as a risk factor. CONCLUSIONS: Albuminuria and retinopathy were highly associated with accumulated metabolic abnormalities including sub-clinical elevated blood pressure and elevated fasting plasma glucose.